The Causality Between Human Resource Planning, Career Development, and Work Achievement of Employees in PT. Peteka Karya Gapura Gorontalo Region - Melan Angriani Asnawi (AIBPM Publisher, 2018)
In the current era, every organization both public and private is required to adapt and open up to changes that are so fast, as well as maximum effort to prepare strategies and various alternative policies which is in line with the times, both the external environment and internal environment. The respondents in this study are heterogeneous based on gender, age, and length of work, education level and so on in total there are 30 people. Respondents were selected as indorman in uncovering the causal relationship between human resource planning, career development, with employee work performance.